2011
DOI: 10.4085/1062-6050-46.1.69
|View full text |Cite
|
Sign up to set email alerts
|

Athletic Trainers' Attitudes Toward Lesbian, Gay, and Bisexual National Collegiate Athletic Association Student-Athletes

Abstract: Context: Researchers have investigated heterosexuals' attitudes toward homosexuals, focusing on factors such as sex, race, religion, education, and contact experiences. However, in the context of sport, this research is deficient. We found no published literature investigating athletic trainers (ATs') attitudes toward lesbian, gay, and bisexual student-athletes (LGB).Objective: To determine heterosexual ATs' attitudes toward LGB student-athletes in the National Collegiate Athletic Association.Design: Cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
27
0
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 22 publications
6
27
0
8
Order By: Relevance
“…Generally, existing research has mostly focused on hostility or inclusivity toward lesbians and gay men within sports (Morrow & Gill 2003;Piedra et al, 2017), has adapted instruments devised for other purposes , has used single items (Drummond et al, 2015;Gill et al, 2010;, or has assessed the sexual prejudice in sports-related contexts without distinguishing it from general sexual prejudice (Anderson & Mowatt, 2013;Ensign et al, 2011;Forbes et al, 2002;Gill et al, 2006;O'Brien et al, 2013;Oswalt & Vargas 2013;Roper & Halloran, 2007;Sartore & Cunningham, 2009). For this reason, the SPSS scale was specifically designed to explore specific sexual prejudice toward LG athletes and coaches and to distinguish certain kinds of attitudes within sports, such as negative attitudes toward coming-out in sports-related contexts or stereotypes about LG athletes' performance.…”
Section: Convergent and Divergent Validity Of The Spssmentioning
confidence: 99%
“…Generally, existing research has mostly focused on hostility or inclusivity toward lesbians and gay men within sports (Morrow & Gill 2003;Piedra et al, 2017), has adapted instruments devised for other purposes , has used single items (Drummond et al, 2015;Gill et al, 2010;, or has assessed the sexual prejudice in sports-related contexts without distinguishing it from general sexual prejudice (Anderson & Mowatt, 2013;Ensign et al, 2011;Forbes et al, 2002;Gill et al, 2006;O'Brien et al, 2013;Oswalt & Vargas 2013;Roper & Halloran, 2007;Sartore & Cunningham, 2009). For this reason, the SPSS scale was specifically designed to explore specific sexual prejudice toward LG athletes and coaches and to distinguish certain kinds of attitudes within sports, such as negative attitudes toward coming-out in sports-related contexts or stereotypes about LG athletes' performance.…”
Section: Convergent and Divergent Validity Of The Spssmentioning
confidence: 99%
“…Los argumentos que se muestran a continuación refuerzan las explicaciones de los trabajos de Eng (2006), Ensign et al (2011) y Roper y Halloran (2007, pues coinciden en señalar a las mujeres como más tolerantes con gays y lesbianas.…”
Section: No Lo Aceptan Pero Lo Respetanunclassified
“…También, el estudio longitudinal con jugadores de rugby y hockey hierba en Reino Unido de Anderson, Mccormack, Lee (2012), resalta la progresiva normalización en los últimos años entendiéndose como la reducción de las actitudes negativas hacia la homosexualidad entre los deportistas, haciéndose cada vez más visibles y siendo aceptados determinados comportamientos y prácticas que antes eran señalados y rechazados para los hombres. En la misma línea, los estudios de Ensign et al (2011) y Oswalt y Vargas (2013 encuentran actitudes positivas hacia los deportistas gays entre los técnicos, aunque persistiendo un pequeño porcentaje de los entrenadores y entrenadoras con actitudes negativas. Estos cambios inclusivos, esta normalización de la homosexualidad que es percibida por los investigadores entre los deportistas y entrenadores, es también señalado por los estudios de Cashmore y Cleland (2012), Cleland 1 y Nylund (2014) entre los fans y los medios de comunicación.…”
Section: Introductionunclassified
“…These results are supported by previous research which revealed that athletic trainers who selfidentified as Catholic or as not having a religious affiliation held more positive views of LGB student-athletes. 8 Rankin and Merson found that a higher proportion of LGB collegiate student-athletes identified with a religious affiliation other than Christian (primarily no religious affiliation) compared to sampled heterosexual athletes. 12 Therefore, it is not surprising that Efficacy Scale scores to coach LGB athletes would be associated with differences in religious beliefs.…”
Section: Religious Affiliationmentioning
confidence: 99%
“…18-29 (0) 30-39 340-49 250+ 5Sexual Orientation: Heterosexual 9Gay 1Ethnicity: Caucasian 7Black 2Asian 1Years Coaching: 1-3 Years 14-6 Years (2) 7-9 Years 010-12 Years (0) 13-15 Years 3Over 15 Years 4Religious Affiliation: Atheist 1Baptist 3Catholic 1Methodist 1No Affiliation 3Unspecified 1Education: Some College (1) 4 Year Degree (4) Graduate School (5) Prev LGB Training: Yes (2) No (8) Sports Coached:…”
mentioning
confidence: 99%